Modified antireflux monoanastomotic laparoscopic gastric bypass in morbid obesity surgery - A. V. Klymenko; V. M. Klymenko; A. I. Bilai; M. V. Nikolaiev (Zaporožskij Medicinskij Žurnal)
Aim: to analyze the results of a modified monoanastomotic gastric bypass technique in patients with morbid obesity.